2016
DOI: 10.1080/1067828x.2016.1153553
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Drinking Initiation Among Latino Youths: Cognitive and Contextual Explanations of the Immigrant Paradox

Abstract: This study examined the immigrant paradox in drinking initiation among Latino youths and tested contextual (i.e., family, peer) and cognitive (i.e., alcohol expectancies, risk-taking) explanations of this pattern. A sample of 129 first-and second-generation (73%) youths completed the study. The estimated odds of starting to drink were 2.5 (95% confidence interval [CI]: 1.10-5.9) times higher for second-generation teens compared to first-generation youths. Negative expectancy valuations and perceptions of peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…The phrase the “immigrant paradox” is a construct related to a phenomenon in which first-generation immigrants exhibit better biopsychosocial outcomes, including lower rates of substance use, than do their native-born peers or second (third and fourth) immigrant generations, despite often living in worse socioeconomic conditions (Bui, 2013; Salas-Wright et al, 2014; Bacio and Ray, 2016). Also, more recent immigrants are generally found to consume less alcohol and to exhibit less excessive drinking than established immigrants and members of native-born populations (Szaflarski et al, 2011; Lee et al, 2013; Sudhinaraset et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The phrase the “immigrant paradox” is a construct related to a phenomenon in which first-generation immigrants exhibit better biopsychosocial outcomes, including lower rates of substance use, than do their native-born peers or second (third and fourth) immigrant generations, despite often living in worse socioeconomic conditions (Bui, 2013; Salas-Wright et al, 2014; Bacio and Ray, 2016). Also, more recent immigrants are generally found to consume less alcohol and to exhibit less excessive drinking than established immigrants and members of native-born populations (Szaflarski et al, 2011; Lee et al, 2013; Sudhinaraset et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Acculturation-related factors, including language preferences, ethnic affiliations, cultural values, and acculturative stress had been shown to be linked to the alcohol immigrant paradox (e.g., Alamilla et al, 2020;Eitle et al, 2009;Gil et al, 2000;see Lui & Zamboanga, 2018b for review). Other findings indicated that peers' substance use, family cohesion, parental MEXICAN IMMIGRANT PARADOX IN ALCOHOL USE 8 involvement, and personal valuation of the negative drinking-related consequences accounted for nativity differences in alcohol use outcomes among Latinx youth (Bacio & Ray, 2016;Maldonado-Molina et al, 2011;Salas-Wright et al, 2016). The state of the science highlighted the importance of exploring the roles of individual and subgroup characteristics and experiences to better understand the nativity differences in alcohol involvement.…”
Section: Immigrant Paradox Of Alcohol Use Among Latinx Americansmentioning
confidence: 99%
“…In addition, these differences map on to differences in drinking behaviors by immigrant generation among youth (23,24,35) and adults [e.g., (25)] that reflect the immigrant paradox in drinking patterns. While we could not test explanations of this paradox directly, these findings are consistent with the hypothesis that exposure to risky behavioral norms and behaviors inherent in youth environments in the U.S. helps explain why first-generation youth report less risky drinking behaviors than later generations (23,24,35). For example, studies have shown that immigrant youth have peer networks that are less prone to drink because they are more likely to have friends who are also immigrants due to placements based on English proficiency at school and a preference for Spanish speaking peers (74)(75)(76).…”
Section: Changing Drinking Cognitionsmentioning
confidence: 99%
“…Recent data indicate that 38% of the Latinx community are first-generation immigrants and only 34% are second-generation immigrant (U.S.-born of parents born in Latin America), while 28% are third-and-later generation immigrant [U.S.-born youth of Latin American ancestry whose parents are U.S.-born; (22)]. First-generation Latinx youth have been found to be less likely to start drinking in adolescence than their second-generation (23,24) and third-and-later generation counterparts (23). Once first-generation youth begin drinking, they seem to drink at the same rate as second generation teens, but first-and second-generation youth report less problematic drinking than their third-and-later generation counterparts (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation